You should reduce the cosine of `143^o` to the cosine of the equivalent angle, located in the quadrant 1 such that:

`cos 143^o = cos (180^o - 143^o) `

You need to expand the right side using the following formula:

`cos(a - b) = cos a*cos b + sin a*sin b`

Reasoning by analogy yields:

`cos (180^o - 143^o) = cos 180^o* cos 143^o - sin 143^o* sin 180^o`

Since `cos 180^o = -1` and `sin 180^o = 0` yields:

`cos (180^o - 143^o) = - cos 143^o`

Substituting `37^o` for `180^o - 143^` o yields:

`cos 37^o = - cos 143^o`

**Hence, reducing to the first quadrant the argument 143^o yields `cos 143^o = -cos 37^o` .**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now